IMPLEMENTASI NILAI NILAI FIQH SIYASAH DALAM PERATURAN DAERAH (PERDA) SYARI’AH - Wahyu Abdul Jafar (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstract: This scientific work was made to find out the implementation of siyasa law fiqh on shari'a regulations. This study is very important because the Syari'ah Regional Regulation which is made without regard to the values contained in fiqh of siyasah will dry up and lose its Islamic spirit. Even the law that is born can actually create injustice and prosperity if it is later applied in the community. After the researcher carried out the study in depth it was found a conclusion that the Sharia law that had implemented the value of the siyasah included Syari'ah Perda that was oriented and obedient to Islamic Shari'a, the Syari'ah Regional Regulation which was oriented to the benefit of the the value of justice and equality of rights, the Shari'a Regional Regulation that avoids elements of persecution and dignity, and the Shari'a Regional Regulation which is based on the principle of deliberation.Keywords: Fiqh Siyasah; Regional Regulation; Syari'ah